ClinicalAccess. Issue 3 (2nd July 2016) - Weyant, Emily
ABSTRACT: ClinicalAccess is a clinical decision support tool released in early 2014. It incorporates some familiar aspects of other clinical decision support tools while adding new elements to its interface, such as the ability for users to submit their own questions. Answers provided by ClinicalAccess are supported by evidence and references from McMaster Plus, other McGraw-Hill products, and links to articles in PubMed, amongst other resources.